Self-deception and poor patient care: A big idea from a Sartrean perspective. (November 2016) - Roberts, Marc
Highlights: Situational explanations are commonly employed to account for poor patient care. From a Sartrean perspective, they are false, self-deceptive forms of bad faith. They disregard the freedom, or critically reflective capacity, of practitioners. They are adopted to evade the moral anguish associated with poor patient care. We should acknowledge and assert our freedom and guard against bad faith.